THE IMPORTANCE OF BODY LANGUAGE AND VOICE DEVELOPING IN EFL CLASSROOMS - Shermamatova , Zaynab Azimjonovna; Kosimova, Anora Shakhriyorovna; Karimova , Maftuna Jamoliddinovna (Educational Research in Universal Sciences, 2023)
Body language is conveying a certain meaning by utilizing action, expression and posture. In the EFL process, the body language of the teacher can help to enhance the effect of sound language. It is an urgent and essential method for teachers in order to learn about their students. Additionally, the teacher can create vivid, emphasic and realistic atmosphere in the classroom by using the body language, and comprehend how body language plays a basic role in the process of teaching learners. Foreign language teachers should be able to not only accomplish and dance for enjoyment or pleasure, but also act as an actor with passionate and meaningful actions, movements and countenance; since being always ordinary and non-emotional teacher cannot organize an attractive and effective condition in the duration of EFL lessons. If the teacher has an ability to use clear, appropriate and proficient body language and voice, it can increase the portion of attentions, interests and accurate understanding of learners in language contents, as well as, give a chance them to build their knowledge by their own consciously.